(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Nature provides a plethora of clean, easily accessible, and plentiful sources of alternativeenergy in the form of solar power. It’s helpful to produce power using solar energy. In Nigeria, a constantpower output is produced between 12 pm and 2 pm due to the constant movement of the sun in the sky.The need of establishing a solar tracking system to improve PV solar panel energy efficiency can’t beover emphasised. The most power is produced when panels face the sun directly. A Solar TrackingSystem That Uses an Arduino Has Been Implemented Using This Work’s Methodology. A photovoltaicpanel (PV) adjusts its position depending on the light intensity sensed by Light Dependent Resistors(LDRs). A servo motor controls the movement of the solar panel in the device. The servo motor is beingcontrolled by the microcontroller, which is interpreting signals sent by the LDRs. The conclusion is thattracking panels generate more energy than stationary panels.